60th anniversary virtual issue. (30th November 2022) - Stratford, Elaine
Abstract : Our anniversary editorial celebrates 60 years of the journal and presents 60 papers, all of them in one virtual issue. We lead with a long commentary on the decadal plan for geography outlined by Steve Turton and Alaric Maude and invite reflection on progress. That crucial agenda paper is followed by editorials from three of our ten virtual issues—these on bushfires, biogeographies, and the inaugural Festschrift for Ruth Fincher. We also feature one of our Antipodean Perspective essays by David Bissell on COVID‐19. Thereafter, there are 54 articles from volumes 51 to 60 for readers to engage with. As we launch this celebratory issue, we also flag important changes to the journal: a vibrant new cover; a font change to account for neurodiverse accessibility needs, and a commitment by us to more in the way of webinars, fascinating new papers, and social media engagements. Please enjoy. Photo by Adi Goldstein.